PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN KANTOR CAMAT SALAK KABUPATEN PAKPAK BHARAT - Burjuna Tumangger; Laba Saor Malum Padang; El Azhari (LPPM Universitas Cipta Mandiri, 2024)
In the context of globalization and rapid economic change, employee performance has become a key element in achieving organizational success. High performance reflects better efficiency, effectiveness and quality in carrying out their duties and responsibilities. The importance of strong organizational commitment in moving employees to be dedicated to the organization and its goals is very relevant. An effective leadership style also plays an important role in forming employee commitment and, therefore, has a positive impact on their performance. Therefore, to achieve success, organizations need to ensure that quality human resources, have strong commitment, and are supported by an appropriate leadership style can make the best contribution in achieving organizational goals. The results of the analysis state that affective commitment, normative commitment, and Continuance commitment together has a significant influence on employee performance, as indicated by the F-count value which is higher than the F-table (61,179 > 4,179) with a low significance level (0.000 < 0.05). Apart from that, the results of the analysis also reveal the distribution of respondents based on gender, education and age at the Salak Pakpak Bharat Subdistrict Office. Thus, this study provides an important contribution to the understanding of the relationship between organizational commitment and employee performance and describes the profile of employee characteristics in the office context.